Planning vehicle routes to optimize fuel consumption - Grozdanović, Predrag; Nikolić, Miloš; Šelmić, Milica (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: Models developed for routing transport vehicles with an environmental focus are predominantly dedicated to reverse logistics or transporting environmentally hazardous cargo. Few models in the relevant literature consider the ecological factors for routing vehicles involved in the distribution of consumer goods. Methods: This paper presents a model for planning vehicle routes to optimize fuel consumption, considering the time windows required for service and payload capacity of vehicles. A heuristic algorithm was developed to minimize fuel consumption. A Simulated Annealing metaheuristic was applied to enhance the solutions obtained by the proposed heuristic. Results: The results from the heuristic algorithm for fuel consumption minimization and the improved results using the Simulated Annealing metaheuristic are presented. All tests were conducted on Solomon’s instances. Conclusion: The developed approach to vehicle routing ensures a compromise between transport companies and ecology. The results show that applying this approach can simultaneously minimize the costs of the transport company and CO2 emissions.